Synthesis of 4′‐C‐(Aminoethyl)thymidine and 4′‐C‐[(N‐Methyl)aminoethyl] Thymidine Nucleosides to Enhance DNA Stability. Issue 9 (8th September 2022) - Chandela, Akash; Ueda, Hiroki; Ueno, Yoshihito
Abstract: Antisense oligonucleotide (ASO) therapeutics target the pathogenic mRNA directly and modulate protein expression. Novel chemical modifications help to improve the action of ASOs with better thermal stability and resistance against nucleases. Oligodeoxynucleotides (ODNs) containing 4′‐ C ‐(aminoethyl)thymidine modifications exhibit efficient and stable hybridization with complementary DNA as well as RNA strands showing remarkably improved resistance against nucleolytic hydrolysis, which makes them promising candidates for antisense therapeutics. This article describes the synthesis of a novel nucleoside analog, 4′‐ C ‐[( N ‐methyl)aminoethyl]‐thymidine (4′‐MAE‐T), 3, and previously reported 4′‐ C ‐aminoethyl‐thymidine (4′‐AE‐T), 2, through a newly designed synthetic route to obtain a high overall yield. This has been established by changing the starting material from thymidine to diacetone‐D ‐glucofuranose and synthesizing the known 4‐ C ‐hydroxyethyl pentofuranose. Conversion of the hydroxy group to an azide functional group through Mitsunobu azidation and performing acetolysis, provide the common intermediate 4‐ C ‐(2‐azidoethyl)‐ribofuranose. Subsequent coupling of the thymine nucleobase with the common intermediate under Vorbrüggen glycosylation conditions provides the corresponding modified nucleoside in high yield. It was subjected for conversion of the azide to an amine by Staudinger reaction and 2ʹ‐deoxygenation using Barton‐McCombie conditions. Debenzylation with Lewis acid and mono‐dimethoxytritylation of the 5ʹ‐OH afforded a fully protected 3ʹ‐OH intermediate for phosphitylation to give the corresponding phosphoramidites. In the case of 4′‐MAE‐T, benzyloxymethyl protection of the N 3 ‐position and methylation were carried out prior to debenzylation. These phosphoramidite monomers were suitable with conventional oligonucleotide synthesis, and imparted ameliorated nuclease resistance, and competent RNase H activity, suggesting its potential utilization in ASO drugs. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of 4‐ C ‐(2‐azidoethyl)‐ribofuranose (6 ) Basic Protocol 2 : Synthesis of 4′‐ C ‐aminoethyl thymidine phosphoramidite (15 ) Basic Protocol 3 : Synthesis of 4′‐ C ‐( N ‐methyl)aminoethyl thymidine phosphoramidite (20 )